2020
DOI: 10.3390/electronics9111810
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network Approach and a Data Augmentation Algorithm to Systematize the Diagnosis of Deep-Vein Thrombosis by Using Wells’ Criteria

Abstract: The use of a back-propagation artificial neural network (ANN) to systematize the reliability of a Deep Vein Thrombosis (DVT) diagnostic by using Wells’ criteria is introduced herein. In this paper, a new ANN model is proposed to improve the Accuracy when dealing with a highly unbalanced dataset. To create the training dataset, a new data augmentation algorithm based on statistical data known as the prevalence of DVT of real cases reported in literature and from the public hospital is proposed. The above is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 92 publications
(176 reference statements)
0
14
0
Order By: Relevance
“…ML has previously been studied for a variety of diagnostic approaches [19][20][21] . Several studies have applied ML in the context of VTE, although these ML applications have focused on developing CDSS that aid clinicians in VTE risk stratification of patients rather than diagnose VTE 12,22 . To the best of our knowledge, our work is a pioneering study that shows the potential benefits of ML for the diagnosis of DVT through imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML has previously been studied for a variety of diagnostic approaches [19][20][21] . Several studies have applied ML in the context of VTE, although these ML applications have focused on developing CDSS that aid clinicians in VTE risk stratification of patients rather than diagnose VTE 12,22 . To the best of our knowledge, our work is a pioneering study that shows the potential benefits of ML for the diagnosis of DVT through imaging.…”
Section: Discussionmentioning
confidence: 99%
“…ML technology has previously been explored in the context of VTE, with several studies having shown the potential for ML clinical decision support systems (CDSS) to add incremental value in improving VTE risk stratification of patients. Most of these proposed CDSS are predominantly based upon the Wells criteria 12 , whilst others are more complex, taking into consideration a broader range of clinical risk factors for VTE as identified in the Caprini model (35 discrete clinical risk factors) 13 , 14 . However, to the best of our knowledge, no prior study has shown the potential benefit of ML to aid in the image-based diagnosis of DVT using ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…All models have been trained with folds in the cross-validation search for model parameters. The value has been selected as a trade-off between the computational complexity (low number of folds leads to faster model selection) and prediction error (high number of folds leads to low prediction error) as discussed in [ 38 , 39 ]. Since the cross validation in this case is only used for primary selection of the model to be trained, the prediction error is not critical and the relatively low number of folds gives satisfactory results.…”
Section: One-dimensional Positioningmentioning
confidence: 99%
“…The prevalence of this condition varies with age. It can cause DVT or pulmonary embolism (PE) in some cases [1,[8][9][10]; thrombosis can also develop in other veins such as the liver, cerebral sinus, retina, and mesenteric veins. Approximately one-third of VTE patients develop a PE, while two-thirds exclusively have DVT [11].…”
Section: Introductionmentioning
confidence: 99%
“…For the reasons stated above, the goal of this research is to propose several ML models that are trained by using a dataset of patients with the condition. It is collected from the state of the art [10] to have good judgment and clinical analysis to determine the diagnosis of DVT in a patient with the symptomatology of the condition, with the purpose of having a timely response and thus saving many lifes. In this research, the well-known Raspberry Pi 4 (RPi4) is employed as the edge-computing device to develop ML models and assess their performance in diagnosing DVT.…”
Section: Introductionmentioning
confidence: 99%